Metacognition as a Reading Strategy in Incoming University Students - Ramirez-Altamirano, Erika Belinda; Salvatierra Melgar, Angel; Yauris-Polo, William Camilo; Guillen-Cuba, Sandy; Huamanquispe-Apaza, Carlos; Lima-Roman, Percy (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Reading and reading comprehension is of great importance for students to be able to grasp the main idea of what they are reading, for which reading strategies are needed. The objective of the research is to analyze and describe the perspectives of the reading strategies they use and how to help entering university students to face their professional studies. The methodology used is descriptive and correlational among its elements, it is of cross-sectional and quantitative approach whose sample are university students entering a professional career, 1181 students were surveyed through an online survey.